ҚУРАМАЛЫ СИСТЕМАДА ӨЗИН ШӨЛКЕМЛЕСТИРИЎШИ ФРАКТАЛЛАР: АДАМ, ТӘБИЯТ, ЖӘМИЙЕТ МЫСАЛЫНДА - Гайыпбаев, Н.Р. (ILIM hám JÁMIYET, 2021)
The article explains the importance of synergetic methodology in modern science using the fractal method reflecting complex phenomena in man, nature and society. Nonlinear, open, self-organizing cases of interdisciplinary synergetic are analyzed. The fractal properties of self-organizing systems using the synergetic method are shown using the example of human existence, society and natural phenomena. Mainly recommended for those interested in philosophy, systematic analysis and methodology.